Evaluation of two morphometric methods of bone loss percentages caused by periodontitis in rats in different locations - de Souza, Daniela Martins; de Prado, Fernanda Almeida [UNESP]; de Prado, Marcela Almeida [UNESP]; da Rocha, Rosilene Fernandes [UNESP]; de Carvalho, Yasmin Rodarte [UNESP] (FapUNIFESP (SciELO), 2010)
Objective: The present study evaluated morphometrically bone loss percentages in experimental periodontitis in rats, comparing different locations (lingual mandible, palatal maxilla and buccal maxilla) and two evaluation methods (distance and area methods). Material and Methods: Ligatures were placed around the maxillary right second molar and around the mandibular right first molar in 14 female Wistar rats. The contralateral molars served as intragroup controls. After 4 weeks, the rats were sacrificed and their mandible and maxilla were removed. The specimens were dissected and stained with methylene blue dye. Bone loss was evaluated by two different methods on the surfaces of the defleshed jaw. In the first method, the distance from the cementoenamel junction (CEJ) to the alveolar bone crest was measured in the roots of teeth associated with ligature. In the second method, the area of bone loss was determined using the alveolar tissue bone, CEJ and the proximal region of roots associated with the ligature as reference. The data were converted to bone loss percentages caused by ligature: (ligated - unligated) × 100/ligated. Results: When comparing the distance and area methods, no statistically significant difference was observed (p>0.05). Both methodologies indicated that the maxilla presented greater bone loss than the mandible and it was more accentuated on the buccal side than on the palatal side (p<0.05). Conclusions: The findings of this study show that both the area and the distance methods can be used to evaluate bone loss caused by ligature placement in rats, and suggest applying the morphometric methodology to the maxilla on the buccal side.
Keywords: Experimental studies; Methodology; Periodontal diseases; Rats